Decentralization and Managerial Performance: A Mediated Budget Participation on the Village Government in West Halmahera Regency - Muhammad Hasnin; Musdar Muhammad; Irfandi Buamonabot (The Winners, 2022)
The research aimed to examine the budgetary participation variable as a mediator on the relationship between decentralization and managerial performance. The sample was determined using a purposive sampling method with the consideration of being involved in budgeting. They were village heads in 159 villages in West Halmahera Regency. The data were collected by a survey with a questionnaire. The used analytical tools are simple regression and hierarchical regression as a statistical analysis and IBM SPSS statistics version 24. The results showed that budgetary participation fully mediates the relationship between decentralization and managerial performance. The conclusion provides three main contributions as well as their implications, namely providing new findings related to budget participation as a mediating variable, terms of age at work, and the level of education.